2020
DOI: 10.1002/lary.28900
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Disorders and Association With Mortality: Results From the NHANES 2009–2010

Abstract: Objectives To determine the prevalence of sleep disorders in the United States and the association between sleep disorders and all‐cause mortality. Methods A cross‐sectional analysis of the 2009 to 2010 National Health and Nutrition Examination Survey (NHANES) and 2015 National Death Index (NDI) was performed. The 2009 to 2010 NHANES national household survey for adults ≥ 18 years was examined for the prevalence of sleep disorders as well as standard demographics and the presence of comorbidities (coronary art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Currently, sleep quality problems have become a more common health problem. Sleep quality problems can cause adverse effects such as drowsiness and fatigue, easily trigger psychological problems such as anxiety and depression, and increase the risk of cardiovascular diseases such as hypertension and coronary heart disease and death [ 29 , 30 , 31 , 32 , 33 ]. Therefore, it is particularly important to develop targeted preventive and intervention measures for non-manual workers in Xinjiang to improve their sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, sleep quality problems have become a more common health problem. Sleep quality problems can cause adverse effects such as drowsiness and fatigue, easily trigger psychological problems such as anxiety and depression, and increase the risk of cardiovascular diseases such as hypertension and coronary heart disease and death [ 29 , 30 , 31 , 32 , 33 ]. Therefore, it is particularly important to develop targeted preventive and intervention measures for non-manual workers in Xinjiang to improve their sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Approximately 7.1–9.8% of the population in the United States have been diagnosed with a sleep disorder. 10 , 11 These patients with sleep disorders reportedly have a 1.5-fold higher mortality rate than the general population with no sleep disorders. 11 Therefore, the prevention and treatment of sleep disorders have become important public health issues.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 These patients with sleep disorders reportedly have a 1.5-fold higher mortality rate than the general population with no sleep disorders. 11 Therefore, the prevention and treatment of sleep disorders have become important public health issues. A previous study reported that critically ill patients often suffer from sleep disturbances due to the development of delirium and the use of sedative agents during sepsis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence suggest that sleep habits are important, modifiable risk factors for non-communicable diseases [ 2 ] which may significantly impact quality of life and overall health status. Specifically, poor sleep health has been associated with metabolic [ 3 ], endocrine [ 4 ] and psychiatric [ 5 ] diseases, as well as all-cause mortality [ 6 ]. Combined with high treatment-related costs from increased health care utilization [ 7 ], it is therefore concerning that the prevalence of sleep disorders has become epidemic [ 8 ].…”
Section: Introductionmentioning
confidence: 99%